THE OLENINSKOE GOLD SULFIDE DEPOSIT (KOLA PENINSULA, RUSSIA) - Volkov A.V.; Novikov I.A. (My University, 2002)
The paper deals with the results of geological-structural, mineralogical-geochemical, thermobaro-geochemical, and isotopic studies of the Oleninskoe gold deposit in the Archean Kolmozero-Voron'ya greenstone belt. According to isotopic dating, pre-ore pegmatoid veins and wallrock metasomatites are of Early Proterozoic age (1.9 Ga); i.e., they are considerably younger than magmatic and metamorphic rocks of the greenstone belt (2.9-2.7 Ga). A peculiar feature of the Oleninskoe deposit is the multistage nature of ore-forming processes from pre-ore metasomatites and pegmatoid veins to auriferous disseminated sulfides and epithermal mineralization. The isotope analysis of sulfide sulfur yielded a great similarity between the Pellapahk and Oleninskoe deposits, as well as their dissimilarity from other deposits of the Baltic Shield. The isotope composition of galena lead from the Oleninskoe deposit is analogous to that from the deposits of the Late Archean greenstone belts of Finland. According to data obtained though thermobarogeochemical studies of non-opaque minerals, pre-ore metasomatites of the deposit formed from low-concentration (1.1 wt %) fluids at a temperature of 350°C, whereas pegmatoid veins, at the temperature of 250-220°C; the temperature interval of 140-200°C and solutions with concentration 22-25 wt % (CaCl 2) were found to correlate with the gold-arsenopyrite mineralization.